Characterization and genomic analysis of a novel E. coli lytic phage with extended lytic activity against S. Enteridis and S. Typhimurium - Zhaoxin Zhong; Yanyan Wang; Huimin Li; Hui Zhang; Yan Zhou; Ran Wang; Hongduo Bao (Food Production, Processing and Nutrition, 2023)
Abstract In order to effectively use of phages as antimicrobial agents for controlling multidrug-resistant E. coli, it is important to understand phage biology. The isolation and research of novel bacteriophages are urgently needed for food safety and animal health. Phage is considered as a novel alternative antibacterial agents and a new way of prevent, control and treat pathogens. In this paper, we isolated and characterized a novel lytic phage from chicken samples, named vB_EscP_vE20 (in brief vE20). We identified vE20 as belonging to the Podoviridae family through morphological and phylogenetic analysis. It had lytic activities against 24 out of 51 different serotypes of clinical E. coli strains, interestingly it also can lyse Salmonella species, such as Salmonella Enteritidis (S. Enteritidis) and Samonella Typhimurium (S. Typhimurium). One step growth curve showed that the latent period and lysis period was 10 min and 60 min, respectively. The burst size of vE20 was about 60 PFU/cell. The phage vE20 survived in a wide range of temperatures (30–60 °C) and pH (3–11). The whole genome size of phage vE20 is 77,938 bps, which is double stranded DNA. There are 121 Open reading frame (ORFs) in total, and the GC-content is 42.17%, without virulence-associated, antibiotic and lysogeny related genes. Phage vE20 has high bactericidal activity in killing E. coli EXG20-1 in cultures containing 4 × 109 cfu/mL in several MOIs culture. The results revealed the promising potential of phage vE20 as attractive candidates for the control of E. coli infections. Graphical Abstract